MODEL DISEMINASI PENERAPAN MOBILE MONEY DI MASYARAKAT PEDESAAN KABUPATEN TASIKMALAYA - Sukmadirana, Edi; Seminar, Kudang Boro; Firdaus, Muhammad; Arkeman, Yandra (Jurnal Aplikasi Bisnis dan Manajemen, 2021)
Tasikmalaya District is one of the West Java regions with good agribusiness potentials in food crops and ruminant livestock. The potentials must be utilized properly to have an impact on regional economic improvements. This research aimed to design a dissemination model for mobile money application in rural communities, especially in Tasikmalaya District, in three sub-districts: Singaparna, Rajapolah, and Ciawi, using a structured approach through Soft System Methodology (SSM). The model must be built in a system, through a four-layered model, with components for each layer: a) Layer-1 consists of values, infrastructure (network, smartphone, merchant), customer capabilities, & regulations; b) Layer-2 consists of institutional support (local government and related agencies); c) Feature, communities, and communication media; d) Sweetener program. In the implementation process, layer-1's readiness is a priority that must be met first, followed by layer-2, layer-3, and layer-4's readiness.Keywords: dissemination model, soft system methodology, mobile money, Tasikmalaya